Specific Minimum Criminal Penalty Regulations For Narcotics And The Purpose Of Their Implementation In The Criminal System: Specific Minimum Criminal Penalty Regulations For Narcotics And The Purpose Of Their Implementation In The Criminal System - Johari, Johari (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Narcotics are substances or drugs derived from plants or synthesized that can cause changes in consciousness, loss of sensation, reduce pain, and lead to dependence. Drug abuse, which is increasingly concerning in Indonesia, has become a problem involving various levels of society, from schoolchildren to government employees. To address this problem, the Indonesian government, through Law Number 35 of 2009 concerning Narcotics, regulates the eradication of drug abuse and illicit trafficking, including the imposition of criminal sanctions with specific minimum penalties. This study examines the provisions of specific minimum penalties in Law Number 35 of 2009 and the purpose of their application in the criminal justice system. The research method used is normative juridical, analyzing relevant laws and literature. The results indicate that the specific minimum penalties in Law Number 35 of 2009 concerning Narcotics aim to reduce the impact of drug abuse and provide a more substantial deterrent effect on perpetrators, thus preventing similar crimes in the future. This provision also seeks to reduce disparities in sentencing and send a clear signal about the importance of drug prevention. Furthermore, the implementation of special minimum sentences is expected to protect the public from the impacts of drug abuse and illicit trafficking, as well as reduce the number of cases. This provision reflects the international trend in regulating criminal sanctions to create social justice and more effective law enforcement, while simultaneously preventing further drug abuse.